Analisis Pengaruh Pendidikan Kesehatan tentang Pentingnya Imunisasi pada Bayi terhadap Tingkat Pengetahuan dan Sikap Ibu - Meyska Widyandini; Melisa Melisa; Neneng Neneng; Dessi Ahirta (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Many mothers do not understand the importance of immunization for babies in the Kereng Bangkirai Health Center, Palangka Raya. The cause of the low immunization coverage is because parents are busy working, lack of time, a low initiative of mothers in bringing their babies to be immunized, lack of information obtained by the public either through mass media, electronic media and extension workers and culture that still relies on traditional birth attendants as delivery assistance, so that not recommend to mothers in labor to immunize their babies. Knowing the influence of health education on the importance of immunization for infants on the level of knowledge and attitudes of mothers in Posyandu Kutum Mekar working area UPT Puskesmas Kereng Bangkirai Palangka Raya. Research design using pre-experimental design. Sampling using purposive sampling. The population in this study were mothers who had babies (0-12) months. A sample of 15 respondents in thePosyandu Kutum Mekar working area UPT Puskesmas Kereng Bangkirai Palangka Raya. Based on the analysis of statistical tests with the Wilxoconmethod, the result of the level of mother’s knowledge after being given health education p value = 0,002<0,05 means Ha is accepted. The results of the mother’s attitude after being health education p value= 0,005<0,05 means Ha is accepted. Wilcoxon test result showed the influence of health education on the importance of immunization for infants on the level of knowledge and attitudes of mothers in Posyandu Kutum Mekar working area UPT Puskesmas Kereng Bangkirai Palangka Raya. From this study can be concluded that there is an influence of health education about the importance of immunization to infants on the level of knowledge and attitudes of mothers. With the existence of this research, it is expected to increase nursing services, especially child nursing, through preventive and promotive efforts to increase immunization coverage.